Cover Image. Issue 2 (10th April 2019) - Blain, Hailey; Sinaii, Ninet; Zeltser, Deena; Lyssikatos, Charalampos; Belyavskaya, Elena; Keil, Margaret; Bluemke, David A.; Stratakis, Constantine; Bandettini, Wiphada Patricia; Lodish, Maya
Abstract : Cover caption The cover image, by Hailey Blain et al., is based on the Original Article Aortic pulse wave velocity in children with Cushing syndrome: A window into a marker of early cardiovascular disease .https://doi.org/10.1002/edm2.54 .